2009
DOI: 10.1111/j.1349-7006.2009.01171.x
|View full text |Cite
|
Sign up to set email alerts
|

Global DNA hypomethylation suppresses squamous carcinogenesis in the tongue and esophagus

Abstract: Genome-wide DNA hypomethylation and concomitant site-specific gene hypermethylation are among the most common molecular alterations in human neoplasia. Previous studies revealed that genetic reduction of the DNA methylation level results in opposing effects on tumor development, depending on the tumor cell type and on the different stages of the tumorigenesis. For instance, reduced levels of DNA methylation in mice strongly inhibited tumor development of the intestine, whereas they induced thymic lymphomas and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 22 publications
1
39
0
Order By: Relevance
“…Genetic suppression of a maintenance DNA methyltransferase (Dnmt1) also suppressed tumor development in some of these models (22,27,28). However, so far, the efficacy of suppression of aberrant DNA methylation was not evaluated in chronic inflammationassociated cancers, in which aberrant DNA methylation is heavily involved (29,30).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic suppression of a maintenance DNA methyltransferase (Dnmt1) also suppressed tumor development in some of these models (22,27,28). However, so far, the efficacy of suppression of aberrant DNA methylation was not evaluated in chronic inflammationassociated cancers, in which aberrant DNA methylation is heavily involved (29,30).…”
Section: Introductionmentioning
confidence: 99%
“…P3761; dosage, 100 mg/kg; Sigma-Aldrich; Merck Millipore, Darmstadt, Germany) 14 days following transplantation of cells. Tumors (50-150 mm 3 ) were excised using a scalpel and surgical forceps. Excised tumor samples were froze in liquid nitrogen and stored in a freezer at -80˚C for subsequent western blotting analysis and methylation-specific polymerase chain reaction (MSP) analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Research in previous decades has demonstrated that the development of human ESCC occurs due to multiple genetic or epigenetic alterations (3). Epigenetic changes, including increased DNA methylation, are considered to be a primary risk factor in human ESCC development (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, hypomorphic expression of Dnmt1 can lead to the development of lymphoma (14). Furthermore, crossing Dnmt1 hypomorphic mice with murine tumor models alters tumor progression, resulting in either increased or decreased tumor development, depending on the disease stage and tissue site (1,7,53). For example, reduced expression of Dnmt1 dramatically decreases intestinal polyp formation in Apc Min/ϩ mice, either alone or in combination with 5-aza-2Ј-deoxycytidine treatment (7,27).…”
mentioning
confidence: 99%